Technology Shocks and Employment in Open Economies - Juha Tervala (Economics: The Open-Access, Open-Assessment E-Journal, 2007)
A growing body of empirical evidence suggests that a positive technology shock leads to a temporary decline in employment. A two-country model is used to demonstrate that the open economy dimension can enhance the ability of sticky price models to account for the evidence. The reasoning is as follows. An improvement in technology appreciates the nominal exchange rate. Under producer-currency pricing, the exchange rate appreciation shifts global demand toward foreign goods away from domestic goods. This causes a temporary decline in domestic employment. If the expenditure-switching effect is sufficiently strong, a technology shock also has a negative effect on output in the short run.
Keywords: E24; F41; E32; 330; Open economy macroeconomics; technology shocks; employment; Technischer Fortschritt; Schock; Makroökonomischer Einfluss; Beschäftigung; Gesamtwirtschaftliche Produktion; Offene Volkswirtschaft; Zwei-Länder-Modell; Allgemeines Gleichgewicht; Theorie